Epidemiological survey from 2009 to 2012 of psoriatic patients in Japanese Society for Psoriasis Research. Issue 3 (8th November 2017) - Ito, Toshihiro; Takahashi, Hidetoshi; Kawada, Akira; Iizuka, Hajime; Nakagawa, Hidemi; ,
Abstract: Since 1982, the Japanese Society for Psoriasis Research has conducted annual epidemiological surveys of patients with psoriasis. Kawada et al . have reported data for 1982–2001 and Takahashi et al . have reported data for 2002–2008. The present study evaluated 9290 psoriatic cases according to age and sex (2009–2012). The male : female ratio was 2.08:1 (6281 male patients [67.6%] to 3009 female patients [32.4%]). The most prevalent type was psoriasis vulgaris (85.6% of all cases), which was followed by psoriasis arthropathica (6.0%), psoriasis guttate acuta (3.2%), Zumbusch‐type generalized pustular psoriasis (1.8%) and psoriasis erythroderma (1.5%). Psoriasis vulgaris was the most prevalent type for all ages, while psoriasis arthropathica and psoriasis guttate acuta were most prevalent among patients aged less than 65 years. The present survey detected an increased number of cases with comorbid diabetes and/or arthritis symptoms compared with the previous surveys. We found that treatments frequently involved topical corticosteroids (89.7% of cases) and vitamin D3 ointments (78.0% of cases), with a notable increase in the use of vitamin D3 ointments. Systemic treatments were used in 33.3% of cases, including cyclosporin (33.6%), etretinate (19.5%), methotrexate (8.6%), infliximab (11.4%), adalimumab (10.9%) and ustekinumab (6.2%). Phototherapy was used in 30.9% of cases. Although psoralen plus ultraviolet A therapy was the predominant phototherapy during previous studies, the present survey revealed that narrowband ultraviolet B therapy was used in 84.5% of phototherapy‐treated cases. Thus, the present survey revealed major changes in treatment trends.